The Coupling of Stride Length and Foot Strike in Running - Thompson, Missy; Hoffman, Kristine; Blythe, Lindsay; Hasler, Rachel; Longtain, Megan (Frontiers in Sports and Active Living, 2022)
Modifying stride length and/or foot strike in running results in mechanical alterations associated with injury risk. Stride length and foot strike have often been treated as independent factors that affect running mechanics, but there is evidence to suggest that they may be coupled. The purpose of this study was to determine if foot strike and stride length are coupled in running, and if so, can these variables be independently manipulated? Additionally, we sought to determine how independently and simultaneously manipulating stride length and foot strike influenced running kinematics and kinetics. Fifteen individuals ran over ground with stride lengths +/– 10 % of their preferred stride length while adopting both a fore/mid foot strike and rear foot strike pattern, as well as running with their self-selected stride length and foot strike when the opposite variable was controlled. Three-dimensional motion capture and force plate data were captured synchronously during the manipulated stride length x foot strike trials. The results indicate that foot strike and stride length are coupled, with shorter stride lengths being associated with a F/MFS and longer stride lengths being associated with a RFS pattern. Impact peak magnitude was primarily dependent on foot strike, with a F/MFS pattern reducing the magnitude of the impact peak force regardless of stride length. Peak vertical and horizontal ground reaction forces were found to be primarily dependent on stride length, with longer stride lengths resulting in increased vertical and horizontal ground reaction forces, regardless of foot strike. It is difficult, but possible, to independently manipulate stride length and foot strike. Clinicians should be aware of the coupled changes in stride length and foot strike.